Student Reading Interest Analysis at MAN 5 Jombang - Moh Faridl Darmawan; Mohammad Patkul Anam (SCHOOLAR: Social and Literature Study in Education, 2021)
The school literacy movement is one form of government awareness of the importance of building a literacy culture in the world of education in order to create a culture of reading and writing in the school environment as an effort to realize long life education. This research aims to inform how important reading activities are to improve insight or knowledge and there are also supporting factors in increasing reading interest such as teachers, students themselves as well as the environment. This article is a case study with a combination method approach is a research method that combines quantitative research methods and qualitative methods. The data was obtained by making observations especially dahulu,then continued with an interview to the manager of the MAN 5 Jombang library Nuryaningtyas.SE mother. The source concerned is considered to know the most about the massah to befound. Mengenai efforts of teachers and in overcoming low interest in reading students. The results showed that which led to low interest in reading students, because students are always lazy, students consider reading boring and many students do not understand the importance of reading books. The effort made by teachers is to give students an understanding of the importance of reading and hold programs and other events that make students like to read asmuch asencouraging participants in theirdidi kin order to meningkatkan interest inreading mereka yakniby givingkan assignment that ismaterial development. Seiring with the importanceof readinginterest, didik participants can meet theneedfor knowledge mereka with the existence of adequateschool library facilities.